Impact of Gini Ratio, Economic Growth and Unemployment on Poverty Levels: A Panel Data Analysis - Tope, Patta; Kasim, Muhammad Yunus; Ichwan, Mohamad (International Journal of Economics and Financial Issues, 2025)
Despite consistently higher economic growth in Central Sulawesi compared to the national average, the region continues to exhibit a higher poverty rate than the national level. This study examines the effects of income distribution, economic growth, and the open unemployment rate on poverty levels across districts and cities in Central Sulawesi following the 2018 disaster caused by the earthquake and tsunami. The variables used in the study include the poverty rate as the dependent variable and the Gini ratio, economic growth, and open unemployment rate as the independent variables, based on a sample from 13 regions over 5 years (2019-2023), totaling 65 observations. Using secondary data obtained from the Central Statistics Agency of Central Sulawesi Province, the study employs a panel data regression method. The findings reveal that, collectively, income distribution, economic growth, and the open unemployment rate significantly influence poverty levels. However, a partial analysis indicates that while the Gini ratio and the open unemployment rate have significant impacts, economic growth does not significantly affect poverty levels. These results provide insights into the economic dynamics of Central Sulawesi and offer a foundation for targeted poverty alleviation strategies in post-disaster contexts.